ANALISIS NILAI PERUSAHAAN: ROE, IO, IOS, FS, CF, DR DAN DPR - Muanifah, Suciati (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
Difficult expansion, influenced by the lack of working capital, and sources from investors. To overcome this problem, the company should increase its value. This study aims to analyze company value factors through the assessment of financial performance. Research method, using quantitative with secondary data, through BEI publication data. The sampling technique uses purposive, as many as 13 companies are listed on IDX. In the analysis, linear regression is used. The results showed that ROE has positive and significant effect on the DPR. IOS has negative and significant effect on the DPR. Size, debt ratio, insider ownership has no significant effect on DPR. DPR has a significant effect on company value. While the cash flow has a negative significant effect. Simultaneously ROE, insider ownership, investment opportunity set, size, cash flow, and debt ratio has a significant effect on DPR with contribution value of 53.7%